Using EMDR to treat intimate partner relationship break-up issues - Rodríguez-Garay, Ainhoa; Mosquera, Dolores (Frontiers in Psychology, 2022)
The Break-Up Aid Procedure (BUAP) is a proposed EMDR intervention designed to address the difficulties that some patients experience when trying to overcome a complex break-up. The procedure aims to not only target the consequences of the break-up, but also the difficulties that may be present in starting a new relationship. The latter is often the case when there are either unresolved consequences from the previous break-up or untreated early adverse experiences. By structuring the treatment in three sequential stages (outlined in this article) and including interventions and adaptations to the standard EMDR protocol, we aim to facilitate the clinician’s therapeutic approach to intervening for this specific presenting concern and maximizing success.